Blow-bubble to produce ceramic ultra-thin films. Issue 5 (1st April 2018) - Zhang, Haitian; Murtaza, Muhammad; Si, Wenjie; Wu, Hui
Abstract: Ceramic ultra-thin film materials have attracted much attention because of their unique performance compared to the bulk materials and their vital applications in electronic devices and catalysts. An easy, effective and facile method to fabricate high quality ceramic nano membranes will significantly stimulate their practical applications. Herein, we report a new "Blow-bubble" process to produce large area freestanding ultra-thin ceramic material. We successfully used a blow-bubble method to obtain large area freestanding ultra-thin ZnO film after thermal process, and this method can also be used to other materials like TiO2. This synthesizing process relies on sol-gel method and surface tension. In summary, this work demonstrates a facile, economic and effective method to fabricate large area freestanding ultra-thin ZnO film. The photoconductivity of the ZnO film was also tested.